Ecosystem‐based fisheries management: A perspective on the critique and development of the concept - Susanna Lidström; Andrew F. Johnson (Fish and Fisheries, 2020)
The concept of ecosystem‐based fisheries management (EBFM) has been subjected to debate since it was introduced in the late 1990s. The development of the concept seems to follow two separate but simultaneous trajectories of increased popularity but also sustained critique. This paper offers an analysis of potential mechanisms behind these disparate trajectories by drawing on a theoretical framework from science and technology studies (STS) centred around "black box" and actor‐network theory. To support our analysis, we perform an exploratory literature review of how the EBFM concept has been used in a selection of high impact fisheries research papers. We find that the popularity of EBFM does not guarantee its integrity, usefulness or analytical insight, but also that persistent critique of how the concept is used seems to be driving some change. We think that a continued trajectory of increased understanding, contextualization and discernibility of EBFM can help overcome the considerable ambiguity associated with the concept and make it increasingly useful to fisheries management. This means moving away from routine use of the term towards a practicable and tangible approach to improve fisheries sustainability.